Conversion of vertically-aligned boron nitride nanowalls to photoluminescent CN compound nanorods: Efficient composition and morphology control via plasma technique. (November 2016) - Wang, B.B.; Zhu, M.K.; Ostrikov, K.; Levchenko, I.; Keidar, M.; Shao, R.W.; Zheng, K.; Gao, D.
Abstract: Two-dimensional BN/CN nanomaterials of various composition and morphology were synthesized in N2 H2 plasma by plasma-enhanced hot filament chemical vapor deposition, with B4 C used as precursor. The results of field emission scanning electron microscopy, X-ray diffractometer, transmission electron microscopy, micro-Raman and X-ray photoelectron spectroscopy evidence that the hexagonal boron nitride nanowalls with carbon and oxide phases were synthesized under about 1:1 ratio of H2 to N2, while the CN nanorods with boron and oxide phases are formed under other ratios of H2 to N2, and the nanowires made of oxide phases are grown without the plasma. Efficient control over the nanostructure composition and morphology was demonstrated, thus proposing a cheap and convenient fabrication technique for the advanced composite boron nitride/graphene materials. The photoluminescence properties of the synthesized BN and CN nanomaterials were also studied using the 325 nm line of HeCd laser as the excitation source. The fabricated nanomaterials can generate the ultraviolet, blue and green multi-PL bands, which are associated to the defects formed in these nanomaterials and the carbon clusters, respectively. These outcomes can make a great contribution to the design of functional BN- and CN-nanomaterials of various morphologies and compositions for the applications in various electronic and carbon-based optoelectronic nanodevices.